Exploring the Mutated Kinases for Chemoenzymatic Synthesis of N[4]-Modified Cytidine Monophosphates. - Kopl?nait?, M.; Butkut?, K.; Stankevi?i?t?, J.; Mekys, R. (Molecules (Basel, Switzerland), 2024)
Nucleosides, nucleotides, and their analogues are an important class of molecules that are used as substrates in research of enzymes and nucleic acid, or as antiviral and antineoplastic agents. Nucleoside phosphorylation is usually achieved with chemical methods; however, enzymatic phosphorylation is a viable alternative. Here, we present a chemoenzymatic synthesis of modified cytidine monophosphates, where a chemical synthesis of novel N[4]-modified cytidines is followed by an enzymatic phosphorylation of the nucleosides by nucleoside kinases. To enlarge the substrate scope, multiple mutant variants of Drosophila melanogaster deoxynucleoside kinase (DmdNK) (EC:2.7.1.145) and Bacillus subtilis deoxycytidine kinase (BsdCK) (EC:2.7.1.74) have been created and tested. It has been determined that certain point mutations in the active sites of the kinases alter their substrate specificities noticeably and allow phosphorylation of compounds that had been otherwise not phosphorylated by the wild-type DmdNK or BsdCK.